KONSEP KEPEMIMPINAN DALAM ISLAM: Karakteristik Pemimpin Ideal Menurut Al-Quran - Arifin, Muhamad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Leadership is an important aspect in managing society and organizations. In the Islamic context, leadership has a deep and special meaning, as documented in the Al-Quran. The Koran is the main guide for Muslims in all aspects of life, including understanding the characteristics of an ideal leader. Therefore, this research aims to explore and analyze the concept of leadership in Islam based on the teachings of the Koran. This research uses a textual analysis method of the Al-Quran with a qualitative approach. The research was carried out by identifying verses from the Koran that refer to the characteristics of an ideal leader, exploring the meaning and messages contained in these verses. The analysis was carried out carefully to reveal relevant leadership principles in Islam. The results of this research identified several characteristics of an ideal leader according to the Koran, including integrity, justice, wisdom, firmness, a sense of responsibility and example. The Koran also emphasizes the importance of leadership based on devotion to Allah. The leadership principles found in the Al-Quran can be adopted and applied in the current leadership context, both in the social and organizational realms.